Determinants of the Availability of Hepatitis C Testing Services in Opioid Treatment Programs: Results From a National Study - Frimpong, Jemima A. (American Public Health Association, 2014)
Objectives. We examined trends and organizational-level correlates of the availability of HCV testing in opioid treatment programs. Methods. We used generalized ordered logit models to examine associations between organizational characteristics of 383 opioid treatment programs from the 2005 and 2011 National Drug Abuse Treatment System Survey and HCV testing availability. Results. Between 2005 and 2011, the proportion of opioid treatment programs offering HCV testing increased but largely because of increases in off-site referrals rather than on-site testing. HCV testing availability was higher in opioid treatment programs affiliated with a hospital and those receiving federal funds. Opioid treatment programs providing both methadone and buprenorphine were more likely to offer any HCV testing, whereas opioid treatment programs providing only buprenorphine treatment were less likely to offer on-site testing. HCV testing availability was associated with more favorable staff-to-client ratios. Conclusions. The increasing use of off-site referrals for HCV testing in opioid treatment programs likely limits opportunities for case finding, prevention, and treatment. Declines in federal funding for opioid treatment programs may be a key determinant of the availability of HCV testing in opioid treatment programs.